Implementation of Financial Accounting Standards (FAS) in Auditing Financial Statements at the Gideon Public Accounting Firm in Medan - Nina Andriany Nasution; Miftha Rizkina; Audy Aulia Ramadini (International Journal of Community Service Implementation, 2025)
Audits related to the recognition and measurement of financial statements in accordance with Financial Accounting Standards (SAK) can improve the quality and accountability of financial statements. This impacts the trust of external parties such as investors and creditors, and helps management in making better decisions. Overall, an effective audit of financial statements in accordance with SAK is a crucial investment in maintaining the integrity and credibility of financial statement information, which contributes to business growth and sustainability. Recognition of audited financial statements in accordance with SAK means that the financial statements have been prepared and presented in accordance with accounting principles applicable in Indonesia, and have been audited by an independent auditor to ensure their reliability. Thus, ensuring that the financial information presented is reliable and provides a clear picture of the entity's financial condition and performance. Financial statements audited by Gideon Public Accounting Firm are measured in accordance with SAK applicable in Indonesia. This audit process involves examining the company's financial statements to ensure their presentation is in accordance with SAK and providing an opinion on the fairness of the presentation. The process of measuring audited financial statements will follow the steps guided by the FAS applicable in Indonesia.